HEALTH EDUCATION TOOL: THE USE OF WHO GROWTH CURVES - Gabel, Felipe; Alves, Eduarda Camila Ferreira; Cruvinel, Giovanna Chiba; Costa, Julia Marjorie Pires; Sarkis, Amanda Inocêncio; Venceslau, Giovanna Fonseca Silva (Seven Editora, 2026)
Monitoring child growth, based on the World Health Organization (WHO) growth charts, is an essential tool for health surveillance and education, allowing for the early identification of nutritional deficiencies and pathologies through the serial analysis of parameters such as weight, height, and head circumference. Developed through a narrative literature review, based on data obtained from PubMed using the descriptor "Growth Curves," this study showed that the practical application of these charts should begin in the prenatal period and extend to postnatal follow-up, highlighting that choosing the appropriate tool is crucial for the pertinent classification of fetal and child development. The results indicate that, although the WHO charts are the global standard, specific populations, such as premature newborns and children with genetic conditions like achondroplasia, require the use of customized third-generation charts to avoid misdiagnoses and reduce parental anxiety. In the discussion, it is emphasized that the objective of these tools is to transform biometric data into visual representations that are understandable for family members, although the professional must consider international growth charts, as well as the biological and environmental factors of each case, avoiding the use of isolated cut-off points as absolute truths. It is concluded that growth charts are cornerstones of modern pediatrics, facilitating clinical-family communication, but their interpretation requires caution and an individualized clinical approach that considers the unique developmental trajectory of each child in their specific context.